(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The use of Ce (iv) is volumetric analysis upto the 1942. Ammonium hexanitratocerate rate (iv) has been described as proposed reference standard and as a primary standard in oxidimetry. It consists of oxidizable cation 2NH4+and complex anionce Ce (No3)6. Which is known to be powerful oxidizing material solutions of hexanitratoceric acid H2Ce (NO3)6in nitric acid are known to be unstable to a minute but measurable extent. A survey of literature revealed that ammonium hexanitratocerate (iv) reagent has not been for carbonys compounds, polyhydric alcohols and sugar. This encourages me to study the reactions of ammonium hexanitratocerate (iv) on carbonyl compounds. Polyhydric alcohols and sugars.